Identification of Domains of the Human Papillomavirus Type 11 E1 Helicase Involved in Oligomerization and Binding to the Viral Origin - Titolo, Steve (American Society for Microbiology, 2000)
The E1 helicase of papillomavirus is required, in addition to host cell DNA replication factors, during the initiation and elongation phases of viral episome replication. During initiation, the viral E2 protein promotes the assembly of enzymatically active multimeric E1 complexes at the viral origin of DNA replication. In this study we used the two-hybrid system and chemical cross-linking to demonstrate that human papillomavirus type 11 (HPV11) E1 can self-associate in yeast and form hexamers in vitro in a reaction stimulated by single-stranded DNA. Self-association in yeast was most readily detected using constructs spanning the E1 C-terminal domain (amino acids 353 to 649) and was dependent on a minimal E1-E1 interaction region located between amino acids 353 and 431. The E1 C-terminal domain was also able to oligomerize in vitro but, in contrast to wild-type E1, did so efficiently in the absence of single-stranded DNA. Sequences located between amino acids 191 and 353 were necessary for single-stranded DNA to modulate oligomerization of E1 and were also required, together with the rest of the C terminus, for binding of E1 to the origin. Two regions within the C-terminal domain were identified as important for oligomerization: the ATP-binding domain and region A, which is located within the minimal E1-E1 interaction domain and is one of four regions of E1 that is highly conserved with the large T antigens of simian virus 40 and polyomavirus. Amino acid substitutions of highly conserved residues within the ATP-binding domain and region A were identified that reduced the ability of E1 to oligomerize and bind to the origin in vitro and to support transient DNA replication in vivo. These results support the notion that oligomerization of E1 occurs primarily through the C-terminal domain of the protein and is allosterically regulated by DNA and ATP. The bipartite organization of the E1 C-terminal domain is reminiscent of that found in other hexameric proteins and suggests that these proteins may oligomerize by a similar mechanism.